Trichloroacetic Acid as a Topical Treatment for Actinic Cheilitis - Victoria Kuta; S. Mark Taylor (OTO Open, 2025)
Abstract Importance Actinic cheilitis is a condition of the lower lip with the potential for malignant transformation. Although many topical treatment options exist, most involve prolonged application periods with expected adverse effects that limit compliance. Objective Trichloroacetic acid is a widely used chemical peel that has been used for the treatment of precancerous skin lesions. This study aims to study the efficacy of 35% trichloroacetic acid as a topical treatment for actinic cheilitis. Study Design Prospective cohort study of patients with actinic cheilitis presenting to our institution between September 2020 and December 2023. After treatment completion, patients were followed twice yearly for a minimum of 2 years. Setting Tertiary care center. Methods All patients with actinic cheilitis presenting to an otolaryngologist‐head and neck surgeon at our institution within the study time frame were eligible. Exclusion criteria include patients <18 years of age, patients who were pregnant, and patients with a biopsy‐proven malignancy of the lip. A topical 35% trichloroacetic acid peel was applied to the lower lip in the minor procedure clinic following bilateral mental nerve blocks. Patients were brought back 1 month later for follow‐up ± a repeat treatment. Photos were taken prior to treatment and 1 month following their final treatment. The severity of actinic cheilitis was graded using a proposed grading scale for actinic cheilitis, and the burden of the condition was assessed using Skindex‐16 Surveys. Visual analog scales were used to study adverse events. Patients were monitored for remission and recurrence. Results A total of 11 patients were enrolled, with the majority requiring one treatment to achieve clinical remission. All patients who completed their full treatment course entered clinical remission following their trichloroacetic acid treatment, and there have been no cases of recurrence to date. The most common reported side effects were redness and swelling. Patients reported a significant improvement in their quality of life following treatment. Conclusion This study suggests that a 35% trichloroacetic acid peel is a safe, well‐tolerated, and effective treatment option for patients presenting with actinic cheilitis. Further follow‐up is indicated to study the longevity of the achieved results. Trial Registration This study is registered on Clinicaltrials.gov (NCT04744103). https://clinicaltrials.gov/study/NCT04744103?locStr=Halifax,%20NS,%20Canada&country=Canada&state=Nova%20Scotia&city=Halifax&cond=actinic%20cheilitis&rank=1.